Surrogate Mother Validity against Children’s Civil Status: Comparative Study, Surrogate Mother in Indonesia and Ukraine - Adinda Permana Putri; Dwi Aryanti Ramadhani (Universitas Kuningan, 2021)
Nowadays, technology is getting more advanced. For example, IVF or